Effects of droplet vitrification on the regeneration of apical shoot tips of mangabeira accessions (Research, Society and Development, 2022)
The mangabeira (Hancornia speciosa Gomes) is a fruit tree of high potential that is distributed in several regions of the Brazil, but which is of great social economic importance for the Northeast region. Due to the wide possibility of using its fruits that can be consumed in natura or industrialized, and that represent a financial source for traditional communities that practice the extractivism of this species. The objective of this study was to evaluate the efficiency of the droplet vitrification technique for the long-term conservation of five mangabeira accessions, as well as to verify if there is any different behavior among the accessions to the possible effects of the cryopreservation process. The apical shoot tips were subjected to different periods (30 and 50 min for test I; 25, 50 and 75 min for test II) of exposure to plant vitrification solution 2 (PVS2) before plunging into liquid nitrogen. To evaluate the effects of cryoprotective solutions and exposed times on apical shoot tips exposed or not exposed to liquid nitrogen, the percentage of regeneration were observed at 30th and 60th day of in vitro cultivation. It was possible to cryopreserve the apical shoot tips from five accessions studied through the droplet vitrification technique. Adjusts must be made in the droplet vitrification technique steps in the pre-culture and post-culture media so that there is a mitigation of the damage caused during the cryopreservation.